2022
DOI: 10.1111/cogs.13138
|View full text |Cite
|
Sign up to set email alerts
|

Copredication in Context: A Predictive Processing Approach

Abstract: We propose a cognitive‐psychological model of linguistic intuitions about copredication statements. In copredication statements, like “The book is heavy and informative,” the nominal denotes two ontologically distinct entities at the same time. This has been considered a problem for standard truth‐conditional semantics. In this paper, we discuss two questions that have so far received less attention: What kinds of word representations and cognitive mechanisms are responsible for judgments about the felicitousn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…(2) by ignoring these variables, the authors make predictions that already face a range of opposing empirical evidence; and (3) it can be shown that predictability bears no statistically significant relation with copredication acceptability, thus undermining the core architecture of the model proposed by Löhr and Michel (2022).…”
Section: Methodological Issuesmentioning
confidence: 99%
See 4 more Smart Citations
“…(2) by ignoring these variables, the authors make predictions that already face a range of opposing empirical evidence; and (3) it can be shown that predictability bears no statistically significant relation with copredication acceptability, thus undermining the core architecture of the model proposed by Löhr and Michel (2022).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…The major methodological issues with the proposal in Löhr and Michel (2022) are as follows: (1) a lack of grounding in specific psycholinguistic variables, such as lexical frequency;…”
Section: Methodological Issuesmentioning
confidence: 99%
See 3 more Smart Citations